INTRODUKSI TEKNOLOGI ROASTING UNTUK MENINGKATKAN PRODUKTIVITAS INDUSTRI KOPI ROBUSTA GUNUNG KELIR - Didik Ariwibowo; Sutrisno Sutrisno; Seno Darmanto; Juli Mrihardjono; Mohammad Endy Yulianto; Riana Sitawati (Sekolah Vokasi Universitas Diponegoro, 2020)
Program for regional superior product (PPUD-DIKTI) year 2020 aims to increase income of coffee farmers who incorporated in Rahayu IV Gunung Kelir by introduction of roaster. This introduction was done by considering that the farmers was potentially developed from coffee bean to coffee powder producers. PPUD was conducted by Teams from LPPM UNDIP. The program was excecuted in steps: i) designing of roaster machine, ii) roaster machine fabrication, iii) implementation, and iv) evaluation. Program evaluation was performed by analyzing to income added from farmers. Roaster was designed dan fabricated with capacity of 3 kg/batch and processing time of 15-20 minutes. After program implementation, the farmers roasted coffee bean by themselves. Therefore, there was a different value between outsider service-roasting, that done before, and self-roasting of Rp. 10.000,-. Besides self-roasting, the farmers commercialize the roaster as roasting services with rates Rp. 15.000,; per kilograms. Result of this PPUD program shows that during 1 month, the farmers earned Rp. 4.250.000,-. This predicted that the earning would increase 4 times because of the roaster operated in 0,25 off capacity by now. This prediction based on a calculation of roaster operating in 20 days and 7 hours effective time per day.